Kompromi dan Interseksionalitas Gender dalam Pemberian Mahar: Tradisi Ampa Coi Ndai pada Suku Mbojo - Atun Wardatun (Ulumuna, 2009)
Ampa Co’i Ndai is a practiced tradition among Suku Mbojo[1] (Bimanese ethnic) where the resource of bride-payment is from the brides, wholly or partially, but it is named after the groom during the declaration of marriage contract. The tradition is, usually, applicable if the social, economic, and/or educational status of brides are higher than that of grooms. Whereas, the ideal expectation of culture and religious norms position men as superior human beings. Gender analysis observes that the tradition is a compromise of the ideal expectation and the real fact of gender relation. In the gender intersectionality’s view, the tradition shows that the male-female relationship should not only be explained merely based on the sexual differences but should be examined comprehensively along with other social categories such as economic, social and educational status. Gender status should be seen as a cross-cutting issue which is inseparable with multi identities of human being. [1]Suku Mbojo adalah nama Suku bagi orang Bima (penduduk bagian paling Timur Nusatenggara Barat dan terletak di pulau Sumbawa).